THE USE OF AUDIO-VISUAL LEARNING MEDIA IN IMPROVING STUDENT CONCENTRATION IN ENERGY MATERIALS - Nia Karlina; Ruli Setiyadi (IKIP Siliwangi, 2019)
Learning Natural Sciences is learning done in elementary schools. During this time, science learning was still difficult for most teachers and prospective elementary school teachers. These difficulties include the difficulties of students in remembering subject matter due to the lack of suitable learning media. In the learning process, teachers should use learning media that can increase students' concentration on the material, in this case, the use of audiovisual media. The purpose of this study was to analyze the difficulties experienced by teachers and prospective teachers in the matter of learning natural science materials. The research method used is quantitative descriptive research method. The study population was 25 elementary school students. The method of data collection is to conduct evaluations conducted in several classroom action research cycles. Classroom learning methods are done classically, students learn by cooperative learning methods. The results showed that audio-visual learning media can be utilized optimally to help students achieve learning goals, and the use of audio-visual learning media is basically intended to make learning activities more effective in learning goals can be achieved well.